Evaluation of seismically induced slope displacement by energy approach and applicability to a Case Study related to the 2016 Kumamoto Earthquake - T. Ishizawa; T. Kokusho (Lowland Technology International, 2018)
The energy approach for slope failure evaluation has been developed by examining the energy balance in the rigid block model, comparing it to innovative shake table tests of sand model slope. As a result, previous studies have shown evaluation method is proposed in which residual slope displacement can be given from the earthquake energy. Moreover, a framework of performance-based design for slopes during earthquakes has been proposed. However, this energy method needs to have more research to upgrade the energy method to a reliable design tool. Therefore, the energy-based method was applied to a case history during the 2016 Kumamoto earthquake. The input earthquake energy defined as a base layer of the slope was extrapolated from severalstrong motion records. This paper discusses applicability of the energy-based method to a case history, during the 2016 Kumamoto earthquake, of the sliding-mass was travelled gentle slope along the clear slip plane, as a simplified rigid block model.